Electrolyte additive for lithium thionyl chloride battery, electrolyte and lithium thionyl chloride battery
By using high-temperature film-forming polymer materials and adjusting the electrolyte and positive electrode current collector structure in lithium thionyl chloride batteries, the problems of safety and service life of the battery at high temperatures are solved, and higher safety and capacity are achieved.
Patent Information
- Application Number
- CN202411347856.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The service life and safety of lithium thionyl chloride high-capacity batteries are difficult to meet the requirements of long-term use and high-temperature environments, and are prone to explosion risk due to short circuits.
The polymer material formed at high temperature is used as the electrolyte additive. It has stable chemical characteristics and is not easy to react with electrolyte and lithium. It forms an insulating film at extremely high temperatures, prevents the reaction between metal lithium and electrolyte, improves battery safety, and passes Adjust the electrolyte composition and positive electrode current collector structure to reduce the risk of short circuit.
Without affecting the long-term service life of the battery, the safety and capacity of lithium thionyl chloride batteries are significantly improved, short-circuit current and temperature are reduced, and the risk of explosion is avoided.
Smart Images

Figure CN119230859A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a lithium thionyl chloride battery and relates to an electrolyte additive for a lithium thionyl chloride battery, an electrolyte and a lithium thionyl chloride battery. Background Art
[0002] Lithium primary batteries are batteries with higher specific energy among current chemical power sources, among which lithium / thionyl chloride is the lithium primary battery with the highest known specific energy. Its characteristics are high operating voltage, which can reach above 3.0V, low battery self-discharge, and easy long-term storage and use. Therefore, it has always been the most widely used battery in commercial applications, such as gas meters, electricity meters, water meters, and the Internet of Things. Under normal circumstances, the battery life is required to be more than 6 years, and the battery must pass relevant safety verification, such as the Atex explosion-proof level must reach T4 (maximum surface temperature 135°C), and even T5 (maximum surface temperature 100°C) or T6 (maximum surface temperature 85°C). Therefore, higher requirements are put forward for the life and safety of lithium thionyl chloride.
[0003] At present, in order to meet the conditions of long-life use, more solutions are used, that is, lithium thionyl chloride high-capacity batteries. This type of battery, due to its carbon-packed structure, can output higher battery capacity at a small current, which is very suitable for the use of IoT meters. However, in many cases, the battery life often does not reach the expected life. The main reasons are as follows: First, affected by the strength of the base station signal, the actual device output power is much greater than the set power, resulting in excessive power consumption and insufficient design life; second, the device chip power consumption is abnormal, resulting in abnormal loss of battery capacity; third, the actual design life of the battery is insufficient or the battery has defects. However, for battery manufacturers, they can only ensure that the battery can output as much capacity as possible by increasing the amount of reactive substances, but this will bring a series of battery safety problems under extreme design conditions.
[0004] Therefore, under the premise of ensuring that the long-term service life of the battery is not affected, improving the safety of lithium thionyl chloride high-capacity batteries is a technical problem that needs to be solved urgently. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide an electrolyte additive, an electrolyte and a lithium thionyl chloride battery for lithium thionyl chloride batteries. The electrolyte additive provided by the present invention is stable at room temperature and is not easy to react with the electrolyte and lithium. When the lithium thionyl chloride battery is subjected to extremely high temperatures, the electrolyte additive of the present invention forms an insulator-like film structure at high temperatures. The film structure is completely attached to the surface of the metallic lithium, preventing the further reaction of the metallic lithium with the electrolyte from releasing a large amount of heat, thereby improving the safety of the battery without affecting the long-term service life of the battery.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides an electrolyte additive for a lithium thionyl chloride battery, wherein the electrolyte additive comprises a polymer material that forms a film at a high temperature.
[0008] The electrolyte additive provided by the present invention includes a polymer material that forms a film at high temperature. The polymer material has stable chemical properties and is not easy to react with the electrolyte and lithium. When the lithium thionyl chloride battery is subjected to extremely high temperature (≥60°C), the polymer material easily forms an insulator-like film that can be completely attached to the surface of metallic lithium, thereby preventing the further reaction of metallic lithium with the electrolyte to release a large amount of heat, thereby improving the safety of the battery without affecting the long-term service life of the battery.
[0009] In the present invention, if the provided additive cannot form a film at high temperature, it cannot block the transfer of electrons. As a result, once the battery is short-circuited, the internal temperature increases, the gas pressure increases, and the battery is at risk of exploding.
[0010] Preferably, the film-forming temperature of the polymer material is 60-100°C, such as 60°C, 70°C, 80°C, 90°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0011] In the present invention, if the film-forming temperature of the polymer material is too low, below 60°C, it will affect the use of the battery in a normal high temperature environment. If it is too high, exceeding 100°C, the additive will not form a film within the normal operating temperature range of the battery (-40°C to +85°C), which will cause a continuous short circuit in the battery and bring safety risks.
[0012] Preferably, the number average molecular weight of the polymer material is ≥10,000, for example, 10,000, 30,000, 50,000, 80,000, 100,000, 130,000, 150,000, 180,000 or 200,000.
[0013] In the present invention, if the number average molecular weight of the polymer material is too low, less than 10,000, the purpose of film formation under a certain high temperature environment cannot be achieved.
[0014] Preferably, the polymer material includes any one of polyvinyl alcohol, polymethyl acrylate, α-cyanoacrylate or methyl methacrylate, or a combination of at least two thereof.
[0015] In a second aspect, the present invention provides an electrolyte for a lithium thionyl chloride battery, the electrolyte comprising thionyl chloride, a lithium salt and the electrolyte additive as described in the first aspect.
[0016] The electrolyte of the lithium thionyl chloride battery provided by the present invention, after adding the electrolyte additive provided by the first aspect, on the one hand, the electrolyte additive has stable chemical properties, is not easy to react with the electrolyte and lithium, and can obtain an insulator-like film at high temperature, which can be completely attached to the surface of the metallic lithium, preventing the metallic lithium from further reacting with the electrolyte to release a large amount of heat, thereby improving the safety of the battery; on the other hand, the proportion of the active substance thionyl chloride can be increased, so that the actual released battery capacity is higher, and at the same time, the concentration of the electrolyte lithium salt is reduced, so that the ion transmission is slower. In extreme cases, the internal reaction of the battery is slower, thereby improving the safety; thereby improving the capacity and safety of the battery.
[0017] In the present invention, if the electrolyte additive provided in the first aspect is not used in the electrolyte of the above system, the purpose of high-temperature film formation cannot be achieved.
[0018] Preferably, the lithium salt includes any one of lithium tetrachloroaluminate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(fluorosulfonyl)imide, lithium tetrachlorogallate or lithium perchlorate, or a combination of at least two thereof.
[0019] Preferably, the electrolyte further comprises a second additive.
[0020] Preferably, the second additive includes any one of sulfur dioxide, polyvinyl chloride, bromine chloride or vinyl chloride-vinylidene chloride copolymer, or a combination of at least two thereof.
[0021] In addition to the electrolyte additive provided in the first aspect, the electrolyte provided by the present invention may also be added with other types of additives (second additives) to reduce the impedance of the positive and negative electrodes and alleviate the voltage hysteresis phenomenon of the battery.
[0022] Preferably, the mass percentage of thionyl chloride in the electrolyte is 85-90%, for example, 85%, 86%, 87%, 88%, 89% or 90%.
[0023] Preferably, the mass proportion of the second additive in the electrolyte is 0.5-1%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.
[0024] Preferably, the mass proportion of the electrolyte additive in the electrolyte is 0.5-1%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.
[0025] In the present invention, if the mass proportion of the electrolyte additive in the electrolyte is too small, less than 0.5%, on the one hand, the additive will be unevenly dispersed in the electrolyte, and on the other hand, the amount of film formed is too small to achieve the purpose of high-temperature electron blocking. If it is too much, if it exceeds 1%, since the additive is a polymer material, it will cause the internal resistance of the battery to increase, affecting the battery discharge performance.
[0026] Preferably, the concentration of the lithium salt in the electrolyte is 0.6-1 mol / L, for example, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L.
[0027] In the electrolyte provided by the present invention, due to the presence of the electrolyte additive of the first aspect, the proportion of thionyl chloride in the electrolyte is significantly increased, thereby increasing the capacity of the battery, while also reducing the concentration of lithium salt in the electrolyte, slowing down the concentration of ion transmission, and improving the safety of the battery.
[0028] In a third aspect, the present invention provides a lithium thionyl chloride battery, wherein the lithium thionyl chloride battery comprises a lithium negative electrode, a separator, a carbon material positive electrode and the electrolyte as described in the second aspect.
[0029] Preferably, the diaphragm comprises a glass fiber diaphragm.
[0030] In the present invention, a glass fiber diaphragm is selected as the diaphragm structure, which has greater tensile strength, higher porosity, and stronger ability to absorb and retain electrolyte; in addition to the above-mentioned glass fiber diaphragm, other types of diaphragms that can be known within a reasonable range by technical personnel in this field are also applicable to the present invention.
[0031] Preferably, the carbon material positive electrode comprises a positive electrode current collector and carbon-coated particles composited on the surface of the positive electrode current collector.
[0032] Preferably, the positive electrode current collector is a single-piece mesh structure.
[0033] Preferably, the material of the positive electrode current collector includes stainless steel.
[0034] The positive electrode current collector provided by the present invention adopts a single-piece stainless steel mesh structure made of stainless steel. Compared with the traditional ring-shaped nickel mesh, its current collecting area is small and the conductivity of stainless steel is lower than that of nickel, which reduces the risk of excessive short-circuit current and improves battery safety.
[0035] Preferably, the raw materials of the carbon-coated particles include acetylene black, conductive carbon black, polytetrafluoro emulsion and solvent.
[0036] In the carbon-coated particles provided by the present invention, except for the binder polytetrafluoroethylene, the carbon-based materials are all homologous. Compared with the traditional composition, the copper powder with metal conductivity or the superconducting carbon black with higher conductivity will be increased. The combination of acetylene black and conductive carbon black provided by the present invention has a smaller electronic conductivity. In the event of an extreme short circuit in the battery, the internal short-circuit current of the battery is smaller and safer. The preparation method of the carbon-coated particles is a conventional technical means, and the carbon-coated particles are obtained by mixing the above raw materials and removing the solvent.
[0037] Preferably, the mass ratio of acetylene black to conductive carbon black is (70-80):(2-3), for example, 70:2, 70:3, 75:2, 75:3, 80:2 or 80:3.
[0038] Preferably, based on the total mass of acetylene black, conductive carbon black and polytetrafluoroethylene emulsion being 100%, the mass of the polytetrafluoroethylene emulsion is 5-10%, for example, 5%, 6%, 7%, 8%, 9% or 10%.
[0039] Preferably, the mass of the solvent is 75-80% of the total mass of the raw material of the carbon-coated particles, for example, 75%, 76%, 77%, 78%, 79% or 80%.
[0040] The lithium thionyl chloride battery provided by the present invention improves the capacity and safety performance of the battery through the special selection of the positive electrode current collector (single-sheet mesh stainless steel), the special selection of carbon-coated particles (acetylene black and conductive carbon black) and the coordination of a specific electrolyte (the electrolyte contains the electrolyte additive provided by the first aspect).
[0041] Need to explain:
[0042] The lithium thionyl chloride battery provided by the present invention, except for the above-mentioned specific limitations, the preparation method of the remaining battery structures, the specific material composition and content, the battery structure (such as the battery also includes a shell and a cover plate, etc.) and the battery assembly method are all conventional technical means, and those skilled in the art can make adaptive selections and adjustments based on the existing technology.
[0043] Exemplarily, the present invention provides a method for preparing a lithium thionyl chloride battery, the preparation method comprising:
[0044] The negative electrode lithium sheet is first wound into a cylindrical shape, then placed in a steel shell, and finally rolled by a mechanical roller to adhere to the inner wall of the steel shell;
[0045] Then put the required glass fiber diaphragm and polytetrafluoroethylene insulation sheet into the steel shell (the glass fiber diaphragm is close to the lithium sheet to block the lithium sheet and the positive electrode carbon package, and the polytetrafluoroethylene insulation sheet is placed at the bottom of the steel shell to play an insulating role);
[0046] After the carbon bag particles are weighed, they are placed in a steel shell and pressed flat into a columnar carbon bag. A diaphragm is placed on the top of the formed carbon bag to prevent the carbon bag particles from spilling out.
[0047] The sheet stainless steel mesh is spot welded on the stainless steel cover assembly, and the cover assembly and the steel shell are pressed together. At the same time, the cover assembly and the steel shell are welded by a laser welding machine.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The electrolyte additive provided by the present invention comprises a polymer material that forms a film at high temperature. The polymer material has a large molecular weight and stable chemical properties. After the electrolyte of a lithium thionyl chloride battery contains the electrolyte additive, it is not easy to react with the electrolyte and lithium. When the lithium thionyl chloride battery is subjected to an extremely high temperature (≥60°C), the electrolyte additive easily forms an insulator-like film that can be completely attached to the surface of metallic lithium, thereby preventing the further reaction of metallic lithium with the electrolyte to release a large amount of heat, thereby improving the safety of the battery without affecting the long-term service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 A comparison chart of the discharge capacity performance of lithium thionyl chloride batteries provided for Application Example 1 and Comparative Application Example 2.
[0051] Figure 2 A comparison chart of short-circuit temperatures of lithium thionyl chloride batteries provided in Application Example 1 and Comparative Application Example 2 after short-circuit testing under extreme conditions.
[0052] Figure 3 A comparison chart of the short-circuit current of the lithium thionyl chloride battery provided in Application Example 1 and Comparative Application Example 2 after short-circuit testing under extreme conditions. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] Example 1
[0055] This embodiment provides an electrolyte additive for a lithium thionyl chloride battery. The electrolyte additive is polyvinyl alcohol PVA (model PVA-117k, film forming temperature of 70-80° C., number average molecular weight of 30,000-40,000).
[0056] This embodiment also provides an electrolyte for a lithium thionyl chloride battery, the electrolyte comprising thionyl chloride, lithium aluminum tetrachloride, sulfur dioxide (a second additive) and an electrolyte additive (polyvinyl alcohol PVA);
[0057] The mass proportion of thionyl chloride in the electrolyte is 85%, the mass proportion of sulfur dioxide in the electrolyte is 0.5%, the mass proportion of polyvinyl alcohol as an electrolyte additive in the electrolyte is 0.5%, and the concentration of lithium aluminum tetrachloride in the electrolyte is 1 mol / L;
[0058] The preparation method of the electrolyte is: thionyl chloride, lithium aluminum tetrachloride, sulfur dioxide (second additive) and electrolyte additive (polyvinyl alcohol PVA) are mixed according to the above mass distribution to obtain the electrolyte of the lithium thionyl chloride battery.
[0059] Example 2
[0060] This embodiment provides an electrolyte additive for a lithium thionyl chloride battery. The electrolyte additive is polymethyl acrylate (model SF01, film forming temperature of 75-85° C., number average molecular weight of 40,000-50,000).
[0061] This embodiment also provides an electrolyte for a lithium thionyl chloride battery, the electrolyte comprising thionyl chloride, lithium aluminum tetrachloride, sulfur dioxide (a second additive) and an electrolyte additive (polyvinyl alcohol PVA);
[0062] The mass proportion of thionyl chloride in the electrolyte is 90%, the mass proportion of sulfur dioxide in the electrolyte is 0.5%, the mass proportion of polyvinyl alcohol as an electrolyte additive in the electrolyte is 1%, and the concentration of lithium aluminum tetrachloride in the electrolyte is 0.6 mol / L;
[0063] The preparation method of the electrolyte is: thionyl chloride, lithium aluminum tetrachloride, sulfur dioxide (second additive) and electrolyte additive (polyvinyl alcohol PVA) are mixed according to the above mass distribution to obtain the electrolyte of the lithium thionyl chloride battery.
[0064] Example 3
[0065] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass proportion of polyvinyl alcohol (PVA) as an electrolyte additive in the electrolyte is 0.8%, and the mass proportion of thionyl chloride in the electrolyte is 87%.
[0066] The components and contents in the remaining electrolytes remain the same as those in Example 1.
[0067] Example 4
[0068] The difference between this embodiment and embodiment 1 is that the electrolyte additive in this embodiment is methyl methacrylate (brand or model TV07138, film forming temperature 75-85° C., number average molecular weight 60,000-70,000).
[0069] The components and contents in the remaining electrolytes remain the same as those in Example 1.
[0070] Example 5
[0071] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass proportion of polyvinyl alcohol, an electrolyte additive, in the electrolyte is 0.3%.
[0072] The components and contents in the remaining electrolytes remain the same as those in Example 1.
[0073] Example 6
[0074] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass proportion of polyvinyl alcohol, an electrolyte additive, in the electrolyte is 1.5%.
[0075] The components and contents in the remaining electrolytes remain the same as those in Example 1.
[0076] Example 7
[0077] The difference between this embodiment and embodiment 1 is that in this embodiment, the mass proportion of thionyl chloride in the electrolyte is 80%.
[0078] The components and contents in the remaining electrolytes remain the same as those in Example 1.
[0079] Example 8
[0080] The difference between this embodiment and embodiment 1 is that the concentration of lithium aluminum tetrachloride in the electrolyte in this embodiment is 1.2 mol / L.
[0081] The components and contents in the remaining electrolytes remain the same as those in Example 1.
[0082] Comparative Example 1
[0083] The difference between this comparative example and Example 1 is that in the electrolyte provided in this comparative example, the mass proportion of polyvinyl alcohol, an electrolyte additive, in the electrolyte is 0%, that is, the electrolyte additive polyvinyl alcohol is not contained.
[0084] The components and contents in the remaining electrolytes remain the same as those in Example 1.
[0085] Comparative Example 2
[0086] The difference between this comparative example and Example 1 is that the electrolyte additive provided in this comparative example is polyvinyl chloride.
[0087] The components and contents in the remaining electrolytes remain the same as those in Example 1.
[0088] The electrolytes provided in Examples 1-8 and Comparative Examples 1-2 were applied to lithium thionyl chloride batteries, as follows.
[0089] Application Example 1
[0090] This application example provides a lithium thionyl chloride battery, which includes a lithium negative electrode, a glass fiber separator, a carbon material positive electrode and the electrolyte provided in Example 1; and also includes a stainless steel housing and a stainless steel cover plate.
[0091] The carbon material positive electrode comprises a positive electrode current collector and carbon-coated particles compounded on the surface of the positive electrode current collector (a single-piece mesh stainless steel structure).
[0092] The raw materials of the carbon-coated particles include acetylene black, conductive carbon black, polytetrafluoroethylene emulsion and solvent. The acetylene black and conductive carbon black are mixed in a mass ratio of 75:2, and then the polytetrafluoroethylene emulsion diluted with deionized water is added to ensure that the proportion of polytetrafluoroethylene emulsion in acetylene black and conductive carbon black is 8% (that is, the total mass of acetylene black, conductive carbon black and polytetrafluoroethylene emulsion is 100%), wherein the weight of deionized water accounts for 80% of the weight ratio of acetylene black, conductive carbon black and polytetrafluoroethylene emulsion (that is, deionized water accounts for 80% of the total mass of the carbon-coated particles), the mixed materials are granulated, and then dried to remove moisture to obtain carbon-coated particles.
[0093] The preparation method of the lithium thionyl chloride battery is as follows:
[0094] (1) The negative electrode lithium sheet is first wound into a cylindrical shape, then placed in a steel shell, and finally rolled by a mechanical roller to adhere to the inner wall of the steel shell, and then the required glass fiber diaphragm and polytetrafluoroethylene insulation sheet are placed in the steel shell;
[0095] (2): After the carbon bag particles are weighed, they are placed in a steel shell and pressed flat into a columnar carbon bag. A glass fiber diaphragm is placed on the top of the formed carbon bag to prevent the carbon bag particles from overflowing.
[0096] (3) spot welding the sheet stainless steel mesh onto the stainless steel cover assembly, and pressing the cover assembly and the steel shell together. At the same time, the cover assembly and the steel shell are welded by a laser welding machine (so that the positive electrode current collector with a stainless steel mesh structure is composited with the carbon-coated particles) to obtain a battery cell structure;
[0097] (4) The electrolyte in Example 1 is injected into the battery structure, and sealing nails are added to the injection port of the battery cell after the injection is completed to perform flat pressure sealing to obtain the lithium thionyl chloride battery.
[0098] Application Example 2-8
[0099] The difference between Application Examples 2-8 and Application Example 1 is that the electrolytes provided in Examples 2-8 are used respectively.
[0100] The rest of the structure and preparation method are consistent with those in Application Example 1.
[0101] Application Example 9
[0102] The difference between this application example and application example 1 is that in this application example, the conductive carbon black is replaced with copper powder.
[0103] The rest of the structure and preparation method are consistent with those in Application Example 1.
[0104] Application Example 10
[0105] The difference between this application example and application example 1 is that the positive electrode current collector in this application example is a mesh nickel mesh.
[0106] The rest of the structure and preparation method are consistent with those in Application Example 1.
[0107] Comparative application example 1
[0108] The difference between Comparative Application Example 1 and Application Example 1 is that this Comparative Application Example uses the electrolyte provided by Comparative Example 1.
[0109] The rest of the structure and preparation method are consistent with those in Application Example 1.
[0110] Comparative Example 2
[0111] The difference between Comparative Application Example 2 and Application Example 1 is that this Comparative Application Example uses the electrolyte provided by Comparative Example 2.
[0112] The rest of the structure and preparation method are consistent with those in Application Example 1.
[0113] The lithium thionyl chloride batteries provided in Application Example 1-10 and Comparative Application Example 1-2 were subjected to performance tests under the following test conditions:
[0114] (a) Test of discharge capacity: at room temperature 23±2℃, test the discharge capacity of the battery with a small current (small current is 20mA) cut off to 2.0V;
[0115] (b) Short-circuit temperature and short-circuit current: Perform short-circuit tests under extreme conditions and record the short-circuit temperature and current of the battery at different short-circuit times. The extreme condition is that the positive and negative electrodes of the battery are directly connected with a copper wire with a resistance of less than 0.1Ω and the short circuit is continued until the battery surface temperature reaches a stable value.
[0116] The test results of the above tests are shown in Table 1.
[0117] Figure 1 The discharge capacity performance comparison diagram of the lithium thionyl chloride battery provided by Application Example 1 and Comparative Application Example 2 is shown. Figure 1 It can be seen that by adopting the battery structure of the present invention, more capacity can be discharged under the same discharge conditions.
[0118] Figure 2 A comparison chart of the short-circuit temperature of the lithium thionyl chloride battery provided in Application Example 1 and Comparative Application Example 2 after the short-circuit test in the extreme end state is shown. Figure 2 It can be seen that when the battery is short-circuited, the temperature of the battery surface varies greatly when different polymer additives are used. This indicates that the film-forming temperature of the polymer additives is different inside this battery system.
[0119] Figure 3 A comparison diagram of the short-circuit current of the lithium thionyl chloride battery provided in Application Example 1 and Comparative Application Example 2 after the short-circuit test in the extreme end state is shown. Figure 3 It can be seen that different internal structures of batteries have different short-circuit currents. Due to the special design of the present invention, the short-circuit current of the battery is smaller and the safety is better.
[0120] Table 1
[0121]
[0122] From Table 1, we can get:
[0123] From the data results of Application Examples 1, 5 and 6, it can be seen that if the proportion of the electrolyte additive provided by the present invention in the electrolyte is too small, it will affect the short-circuit temperature of the battery surface, causing the short-circuit temperature to be too high and the short-circuit current to be too large; if the mass proportion is too large, the battery discharge capacity will be low.
[0124] From the data results of Application Examples 1, 7 and 8, it can be seen that the electrolyte additive provided by the present invention not only plays a role in forming a film at high temperature to improve battery safety, but also plays a role in regulating the content of thionyl chloride and lithium salt. If the content of thionyl chloride is too little or too much, the battery capacity will be reduced, and the short-circuit current and temperature will increase.
[0125] From the data results of Application Examples 1 and 9, it can be seen that the carbon-based materials homologues are selected in the carbon-coated particles, and the electronic conductivity of the carbon materials is weaker than that of the copper powder. Therefore, when a short circuit occurs in the battery, the short-circuit current of the battery containing the copper powder system is larger, so the battery surface temperature is higher, and the safety will be weaker than that of the carbon-based materials homologues.
[0126] From the data results of Application Examples 1 and 10, it can be seen that the present invention uses a single-piece mesh stainless steel structure positive electrode collector. Compared with the traditional ring structure current collector, the reaction area of the present invention is smaller. Therefore, the short-circuit current of the battery is smaller and the surface temperature rise is lower.
[0127] From the data results of Application Example 1 and Comparative Application Example 2, it can be seen that if the corresponding electrolyte additive that forms a film at high temperature is not added to the electrolyte provided by the present invention, the purpose of reducing the short-circuit current and temperature of the battery cannot be achieved; and if other types of additives are added (that is, the effect of film formation at high temperature cannot be achieved), the purpose of reducing the short-circuit current and temperature of the battery cannot be achieved either.
[0128] In summary, the electrolyte additive provided by the present invention includes a polymer material that forms a film at high temperature. The polymer material has a large molecular weight and stable chemical properties. After the electrolyte of the lithium thionyl chloride battery contains the electrolyte additive, it is not easy to react with the electrolyte and lithium. When the lithium thionyl chloride battery is subjected to extremely high temperature (≥60°C), it is easy to form an insulator-like film, which can be completely attached to the surface of the metallic lithium, preventing the metallic lithium from further reacting with the electrolyte to release a large amount of heat, thereby improving the safety of the battery without affecting the long-term service life of the battery.
[0129] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. An electrolyte additive for lithium thionyl chloride batteries, characterized in that: The electrolyte additive includes a polymer material that forms a film at high temperature.
2. The electrolyte additive for lithium thionyl chloride battery according to claim 1, characterized in that: The film-forming temperature of the polymer material is 60 to 100°C; Preferably, the number average molecular weight of the polymer material is ≥10,000; Preferably, the polymer material includes any one of polyvinyl alcohol, polymethyl acrylate, α-polycyanomethyl acrylate or polymethyl methacrylate, or a combination of at least two thereof.
3. An electrolyte for a lithium thionyl chloride battery, characterized in that: The electrolyte comprises thionyl chloride, a lithium salt and the electrolyte additive as claimed in claim 1 or 2.
4. The electrolyte of the lithium thionyl chloride battery according to claim 3, characterized in that: The lithium salt includes any one of lithium tetrachloroaluminate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(fluorosulfonyl)imide, lithium tetrachlorogallate or lithium perchlorate, or a combination of at least two thereof.
5. The electrolyte of the lithium thionyl chloride battery according to claim 4, characterized in that: The electrolyte further includes a second additive; Preferably, the second additive includes any one of sulfur dioxide, polyvinyl chloride, bromine chloride or vinyl chloride-vinylidene chloride copolymer, or a combination of at least two thereof.
6. The electrolyte of the lithium thionyl chloride battery according to claim 5, characterized in that: The mass proportion of thionyl chloride in the electrolyte is 85-90%; Preferably, the mass proportion of the second additive in the electrolyte is 0.5-1%; Preferably, the electrolyte additive accounts for 0.5-1% by mass in the electrolyte; Preferably, the concentration of the lithium salt in the electrolyte is 0.6-1 mol / L.
7. A lithium thionyl chloride battery, characterized in that: The lithium thionyl chloride battery comprises a lithium negative electrode, a separator, a carbon material positive electrode and an electrolyte as claimed in any one of claims 3 to 6.
8. The lithium thionyl chloride battery according to claim 7, characterized in that: The carbon material positive electrode comprises a positive electrode current collector and carbon-coated particles compounded on the surface of the positive electrode current collector.
9. The lithium thionyl chloride battery according to claim 8, characterized in that: The positive electrode current collector is a single-piece mesh structure; Preferably, the material of the positive electrode current collector includes stainless steel.
10. The lithium thionyl chloride battery according to claim 8 or 9, characterized in that: The raw materials of the carbon-coated particles include acetylene black, conductive carbon black, polytetrafluoro emulsion and solvent; Preferably, the mass ratio of acetylene black to conductive carbon black is (70-80):(2-3); Preferably, based on the total mass of acetylene black, conductive carbon black and polytetrafluoroethylene emulsion being 100%, the mass of the polytetrafluoroethylene emulsion is 5 to 10%; Preferably, the mass of the solvent is 75-80% of the total mass of the raw material of the carbon-coated particles.
